Botulinum Toxin Treatment in Clinical Medicine A Disease-Oriented Approach (Springer International Publishing, 2018)
This book provides BoNT treatment menus for symptom-oriented therapy in 14 different disease categories. Each chapter starts with a brief description of the disease and its current treatment followed by an evidenced-based review of BoNT efficacy for the symptom(s) of that disease. The level of efficacy is provided based upon the published assertions of the Therapeutic Subcommittee of the American Academy of Neurology. Each chapter includes case histories from the editor's vast experience of over 25 years with BoNT therapy and descriptions of injection techniques enhanced by illustrative figures. Botulinum Toxin Treatment in Clinical Medicine provides an additional introductory chapter that discusses molecular structure, mechanism of action, toxin serotypes, immunogenicity and safety issues. Meanwhile, a concluding chapter provides information on potential future application of these toxins for treating symptoms of other specific diseases.